2023
DOI: 10.29244/jtcs.10.1.79-85
|View full text |Cite
|
Sign up to set email alerts
|

Response of Lettuce (Lactuca sativa L.) To Aquaculture Wastewater Treatment

Abstract: The fish feed waste and litters are organic matter that can be a source of nutrients for plants. This study is aimed to determine the growth and production of lettuce (Lactuca sativa L.) treated with wastewater from hard-lipped barb culture of several population densities. The research was carried out from April through June of 2020 at the greenhouse of the Agrotechnology Study Program, Faculty of Agriculture, Djuanda University, Bogor, Indonesia. The controlled study used a randomized block design with one fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to the analyzed results shown in Table 5, the highest plant height was observed in plants grown with Albert's solution (T2) and lowest plant height was observed in plants grown with water (T1) from 2 nd week to 6 th week after establishment of lettuce in the aquaponic system. Mumpuni et al [22] also found out that lettuce plants when treated with AB mix grows taller compared to fish waste water treatment. In the present study, the plants grown in T3, T4 and T5…”
Section: Plant Heightmentioning
confidence: 97%
“…According to the analyzed results shown in Table 5, the highest plant height was observed in plants grown with Albert's solution (T2) and lowest plant height was observed in plants grown with water (T1) from 2 nd week to 6 th week after establishment of lettuce in the aquaponic system. Mumpuni et al [22] also found out that lettuce plants when treated with AB mix grows taller compared to fish waste water treatment. In the present study, the plants grown in T3, T4 and T5…”
Section: Plant Heightmentioning
confidence: 97%